Penggunaan Media dalam Pembelajaran Matematika: Literature Review - Habiba Ulfahyana; Sape, Herwandi (Almeera Education, 2024)
This research aims to explore the use of various types of media in mathematics learning. This research will examine the effectiveness, benefits and challenges faced in implementing learning media in mathematics classes. Research subjects are individuals, groups, or objects that are the main focus in a study. There are four types of research found in this research, namely Research and Development (R&D), Classroom Action Research, Qualitative Research and Quantitative Research. Based on the description of the article in this research, it was found that students' perceptions of the use of media in mathematics learning were very good, as were the teachers'. However, the use of learning media is still relatively low for several articles. This is due to the lack of competency development and training for teachers. Therefore, it is hoped that teachers can follow the increasingly rapid development of technology and by using media they can attract and direct students' attention to concentrate on lessons.